(untitled) (Lex localis - Journal of Local Self-Government, 2025)
In recent decades and beyond, there has been a global focus on the significance of reading. This is because reading is seen not only as a means to expand one’s knowledge, culture, and language, but also as a way to improve critical thinking, express personal ideas, share knowledge, and offer perspectives based on the material being read. Consequently, various methods and techniques have been proposed to make the teaching of English as a Foreign Language in the context of reading more engaging. With this in mind, this article aims to explore the impact of PDP reading strategies on the students’ reading comprehension and reading response journal writing. It is hypothesized that the implementation of PDP reading strategies in reading narrative books in a reading class would enhance the students’ reading comprehension and would smooth the reading response journal writing. With the intention of meeting with the research’s aims, the descriptive correlational design is applied and two main tools are selected: the structured observation and the questionnaire. One group out of five First year students of English, in the department of English at the University of Kasdi Merbah, Ouargla, within the academic year 2022/2023, was the sample that was given a pre questionnaire before the classroom observation with the intention of having an idea about the students’ insights towards reading in general; their reading preferences and their reading frequency together with gathering information about the students’ perceptions and views about the subject of reading. Then, during the classroom observation that took five weeks, the sample was observed with the purpose of having an idea about the the impact of PDP reading strategies on the students’ reading comprehension and reading response journal writing. The students were provided with an overview of reading comprehension and reading strategies, specifically the PDP, and were guided to write their own reading response journal after having read the novel of the Alchemist of Paolo Coelho within one month. After that, the post questionnaire was conducted and administered with the intention of surveying the students’ views about the impact of the PDP reading strategies on their reading comprehension skills and the PDP reading strategies effectiveness in enhancing them write their reading response journal. The analysis of the results obtained from both the questionnaire and the classroom observation go hand in hand with the research’s aim and affirm that the PDP reading strategies do enhance students’ reading comprehension and reading response journal writing.